Uncovering the treatable burden of severe aortic stenosis in the UK. Issue 1 (26th January 2022) - Strange, Geoffrey A; Stewart, Simon; Curzen, Nick; Ray, Simon; Kendall, Simon; Braidley, Peter; Pearce, Keith; Pessotto, Renzo; Playford, David; Gray, Huon H
Abstract : Objective: To estimate the population prevalence and treatable burden of severe aortic stenosis (AS) in the UK. Methods: We adapted a contemporary model of the population profile of symptomatic and asymptomatic severe AS in Europe and North America to estimate the number of people aged ≥55 years in the UK who might benefit from surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI). Results: With a point prevalence of 1.48%, we estimate that 291 448 men and women aged ≥55 years in the UK had severe AS in 2019. Of these, 68.3% (199 059, 95% CI 1 77 201 to 221 355 people) would have been symptomatic and, therefore, more readily treated according to their surgical risk profile; the remaining 31.7% of cases (92 389, 95% CI 70 093 to 144 247) being asymptomatic. Based on historical patterns of intervention, 58.4% (116 251, 95% CI 106 895 to 1 25 606) of the 199 059 symptomatic cases would qualify for SAVR, with 7208 (95% CI 7091 to 7234) being assessed as being in a high, preoperative surgical risk category. Among the remaining 41.6% (82 809, 95% CI 73 453 to 92 164) of cases potentially unsuitable for SAVR, an estimated 61.7% (51 093, 95% CI 34 780 to 67 655) might be suitable for TAVI. We estimate that 172 859 out of 291 448 prevalent cases of severe AS (59.3%) will subsequently die within 5 years without proactive management. Conclusions: These data suggest a high burden of severe AS in the UK requiring surgical or transcatheter intervention that challenges the ongoing capacity of the National Health Service to meet the needs of those affected.